Classical Greek Models of the Gospels and Acts Studies in Mimesis Criticism - Bilby, Mark G.; Kochenash, Michael; Froelich, Margaret (Claremont Studies in New Testament and Christian Origins, 2018)
Critical studies in the manner in which the New Testament writers immitated classical Greek literature